(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This paper considers ethnocultural and esthetic concepts. Japanese cultural processes and philosophical views are revealed on the example of the concepts of “wabi”, “sabi”. And also, the significance of ethnocultural concepts in Japanese poetry and theater is laid out.